Short-term outcome and predictors of post-operative complications following transurethral resection of the prostate among patients with benign prostate hyperplasia in Northern Tanzania: a prospective analytical study - Esther E. Lekei; Jasper S. Mbwambo; Frank Bright; Magreth Elias; Zerra I. Cheyo; Alfred Kien Mteta; Orgeness Mbwambo; Bartholomeo Nicholaus Ngowi (African Journal of Urology)
Abstract Background Benign prostatic hyperplasia (BPH) is a common condition among elderly men, often presenting with lower urinary tract symptoms. Although transurethral resection of the prostate (TURP) is considered the gold standard for surgical management, outcomes and complication rates vary by setting. This study aimed to assess the short-term outcomes of TURP and identify factors associated with post-operative complications among patients with BPH in Northern Tanzania. Methods This hospital-based prospective analytical study was conducted at Kilimanjaro Christian Medical Centre from January to April 2023. All men with histologically confirmed BPH who underwent TURP were followed for 30 days. Data were analysed using SPSS version 25. Changes in IPSS and QoL were assessed using paired t tests. Logistic regression was used to identify factors associated with post-operative complications. Results A total of 181 patients underwent TURP; 2 (1.1%) patients had lost to follow-up, and 33 (18.2%) had prostate cancer (PCA) after histology results hence excluded from the analysis. The average change of IPSS score was 78.42% ± 18.62 (P ≤ 0.001), while for QoL was 76.22 ± 30.96 (P ≤ 0.001) hence significant improvement. Overall, 86 (58.9%) patients had at least one complication post-operative. Clot retention is the most common complication others mentioned are excessive bleeding requiring transfusion, TUR syndrome, UTI, and failure to void postoperatively after catheter removal. Among the determinants of complications post-TURP were surgery duration of more than 60 min and participants who did not receive medical management pre-operatively and this relation was statistically significant. About 20 (13.7%) of patients failed to void after catheter removal and revisited the hospital within 30 days after TURP. Among revisit patients 13 (65%) had a repeat procedure of TURP, clots evacuation in theatre 3 (15%), and 4 (20%) were catheterized to assist with regaining bladder capacity function. Conclusions TURP significantly improves IPSS and QoL scores in most patients. Clot retention was the most frequent complication. Prolonged surgical time and absence of preoperative treatment increased complication risks. Good surgical techniques and practices can minimize complications, such as clot retention and TUR syndrome.